PERHITUNGAN KOEFESIEN PINDAH PANAS PADA HEAT EXCHANGER UNTUK PENGERINGAN - Suntoro, Dedi; Kindi, Hablinur Al- (AME (Aplikasi Mekanika dan Energi): Jurnal Ilmiah Teknik Mesin, 2016)
Hot air from residual biomass combustion in biomass power plant can be used for drying process. In this study, hot air from residual biomass combustion was utilised as energy source for tray dryer. Model of tray dryer developed by Boiler Laboratory, Lemigas was used as drying apparatus. The objective of this study was to analyze the distribution of hot air inside tray dryer using Computational Fluid Dynamic (CFD). Heat transfer occurs in heat exchanger. Hot air coming from heat exchanger to dryer by be blown with blower. One of the most important variable is heat transfer coefficient in heat exchanger (U).This research aims to find heat transfer coefficient in heat exchanger . The result , heat transfer coefficient depend on five thermal resistance ; thermal resistance by air convection 0,011 m2.K/W, thermal resistance by factor of air pollutant 0,00035 m2.K/W, thermal resistance by flue gas pollutant 0,00176 m2.K/W, thermal resistance by conductivity material , thermal resistance by flue gas 0,03 m2.K/W. Heat transfer coefficient is 23.55 W/m2 .K .